Elasto-plastic finite element analysis of isotropic plates with U-notches - Arslan, Nurettin; Turgut, Aydin; Sancaktar, Erol (My University, 1996)
Elasto-plastic stress analysis of the U-notched Isotropic steel plates (SAE 1060) has been carried out using the finite element method (FEM). Isoparametric rectangular elements with four nodes have been employed and the Lagrange polynomial has been used as interpolation function. Mechanical properties and yield strength of the U-notched plates have been obtained experimentally using a tensile testing machine. The spreads of the plastic zones have been illustrated for varies cases Residual stress and equivalent stresses obtained have been presented in diagrams and compared with some of the relevant studies in the literature. The tensile loads of the isotropic plates with U-notches have been shown to increase due to residual stresses which take place under plane stress conditions.
Keywords: Elasticity; Interpolation; Lagrange multipliers; Mechanical properties; Plasticity; Plates (structural components); Polynomials; Residual stresses; Stress analysis; Tensile testing; Elasto plastic finite element analysis; Equivalent stresses; Isotropic plates; Lagrange polynomial; Plastic zones; Finite element method